Electrochemistry in Medicine: Graphene and Celular Electrostimulation - Villarreal Valdiviezo, Griselda Patricia; Múzquiz Ramos, Elia Martha; Gallardo Heredia, Marisol; Ríos Hurtado, Jorge Carlos (Revista Mexicana de Ingenieria Biomedica, 2024)
The use of cellular electrostimulation in medicine has been an increasingly growing area of interest, and graphene has emerged as a promising material in this field. This article explores how cellular electrostimulation can influence key biological processes and how graphene, with its unique properties, can enhance this technique. The electrochemical aspects of the graphene-cell interaction and its impact on cellular activity regulation were investigated. Additionally, various applications of graphene in cellular electrostimulation, from tissue engineering to disease treatment were examined. This article provides a comprehensive insight into how the combination of electrochemistry and graphene is transforming the field of regenerative medicine.